Evaluation of DC machine armature winding temperature estimation using temperature measured on brush and bearing - Mohd Azri Hizami, Rasid; Muhammad Nor Azril, Zulkafli; Daing Mohamad Nafiz, Daing Idris (Institute of Electrical and Electronics Engineers Inc., 2022)
The armature of a dc machine rotates inside the machine, making it expensive and complex for physical temperature instrumentation and visual thermography. A real-time temperature estimator using the temperature data measured on non-moving parts like the brush and bearing could be developed by determining beforehand the temperature difference between the winding and the brush or bearing. This study evaluates the temperature difference between the armature winding in comparison to the temperatures of the brush and the bearing. It is shown that the temperature difference are much higher between the winding and bearing in comparison to the temperature difference between the winding and the bearing. The temperature differences increase with the increase of losses, at 26.9C and 13.8 C for winding-bearing and winding-brush average tem-perature differences respectively. It was also shown that the temperature gradient on a component can have a large range, leading to an error of estimation depending on the positioning of the thermocouple. The error computed using the error of the sum shows an estimation error for the winding temperature estimated by the bearing temperature and the brush temperature to be at 14.22C and 12.9C respectively at a current of 5A. These results show the impracticality of the armature winding temperature estimator proposed.